2018
DOI: 10.1016/j.idc.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Respiratory Viruses in Children

Abstract: Respiratory viral infections are a leading cause of pediatric disease. Emerging respiratory viruses can cause outbreaks with significant morbidity and mortality or circulate routinely. The rapid identification of pathogens, epidemiologic tracing, description of symptoms, and development of preventative and therapeutic measures are crucial to limiting the spread of these viruses. Some emerging viruses, such as rhinovirus C and influenza C, circulate yearly but were previously undetected due to limited diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Rather than RSV, we found that IgM of INFB ranked 2nd at 27.77% of the pathogens examined, while RSV was only 1.6%. The specific distribution is possibly due to the varied region or enthics [25] since data from other studies showed that 18.7% tested positive for influenza virus out of 666,493 specimen in the USA [26]. while H3N2 viruses predominated in the southeastern United States, only small numbers of < 3% INFB were reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than RSV, we found that IgM of INFB ranked 2nd at 27.77% of the pathogens examined, while RSV was only 1.6%. The specific distribution is possibly due to the varied region or enthics [25] since data from other studies showed that 18.7% tested positive for influenza virus out of 666,493 specimen in the USA [26]. while H3N2 viruses predominated in the southeastern United States, only small numbers of < 3% INFB were reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Schuster et al, pediatric cases could be infected with MERS-CoV secondarily as they were contacts of adults with MERS. Adults become infected with MERS-CoV at the workplace or due to contact with intermediate host animals ( Schuster and Williams, 2018 ).…”
Section: Transmission and Source Of Infectionmentioning
confidence: 99%
“…A very advantageous instrument for distinguishing SARS infected children from the others is real-time reverse transcription-polymerase chain reaction (RT-PCR). RT-PCR is also used for MERS-CoV nucleic acid detection, too ( Schuster and Williams, 2018 ). It takes a few hours for the test to count the RNA viruses in the serum ( Li and Ng, 2005b ).…”
Section: Diagnosismentioning
confidence: 99%
“…Diagnosis of emerging and novel viruses, including HBoV, RV-C, coronaviruses (e.g., HCoV-HKU1, HCoV-NL63, SARS-CoV-2) as well as specific subtypes of AIV (H5N1, H7N9, H10N8) and reassortant IAV strains remains challenging (Schuster and Williams, 2018;WHO, 2020a). The diagnosis of most of these viruses is based on molecular techniques that can only be performed at specialized referral centers.…”
Section: Commercially Available Test Systemsmentioning
confidence: 99%
“…NAATs have higher sensitivity than immunochromatographic assays, but generally, they require a higher degree of technical skills and training (Drancourt et al, 2016). Polymerase chain reaction (PCR) remains the gold standard technique for the diagnosis of AIV subtypes while WHO recommends against the utilization of rapid tests in avian flu diagnosis (WHO, 2005;Monne et al, 2008;Schuster and Williams, 2018). RV-C, is typically detected from nasopharyngeal specimens using reverse transcriptase PCR (RT-PCR) and specific species and serotypes can be further identified by semi-nested PCRs or sequencing (Bochkov et al, 2011;Jartti et al, 2012;Schuster and Williams, 2018).…”
Section: Commercially Available Test Systemsmentioning
confidence: 99%